The comb’s composite materials for bearing building constructions - Матченко, Т. І.; Мурга, В. Є. (Proceedings of National Aviation University (archive), 2021)
The constructive scheme of selling composite materials for building constructions was proposed, which have next properties: great hardness and firmness on compression and bending, heat resistance, stable to creepage and small density.